2017
DOI: 10.1016/j.devcel.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Converging DNA Methylation Pathways in Placenta and Cancer

Abstract: CpG island promoters are generally devoid of DNA methylation in somatic cells but are frequently methylated during tumorigenesis. Reporting recently in Nature, Smith et al. (2017) show that the signaling-induced methylome in early extraembryonic tissues resembles that of many cancers, suggesting that placental nuclear programming might be co-opted in tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…Increasing evidence has shown that epigenetic regulation, such as abnormal hypermethylation of CpG islands in promoters, is key to tumorigenesis [48]. In our study, the genes, corresponding to 437 specific methylation sites in the promoter region were considered for TF enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that epigenetic regulation, such as abnormal hypermethylation of CpG islands in promoters, is key to tumorigenesis [48]. In our study, the genes, corresponding to 437 specific methylation sites in the promoter region were considered for TF enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using a similar approach, a decision-tree model incorporating also -hCG levels was built; this is shown in Suppl. Human placentation is an intricate process of fetal-maternal interaction that shares some similarities with cancer migration and metastasis (35). In this context, kisspeptins, initially identified as potential metastasis-suppressing factors abundantly expressed in the placenta, were suspected as important players for the fine control of trophoblast invasion and placentation (17,18).…”
Section: Circulating Kisspeptin/mir-324-3p As New Early Biomarker Of Epmentioning
confidence: 99%
“…Approximately half of bivalent promoters with a high PDR in MM are associated with PC-PMDs. Therefore, the DNA methylation landscape of MM resembles that of the placenta, with stochastic methylated gain in CGIs embedded in large hypomethylated regions, suggesting that, as in other cancers, myeloma cells coopt placental nuclear programming [48,49]; this finding is of particular interest since placental and cancerous tissues share relevant features such as immune modulation, angiogenesis and tissue invasion [50]. Interestingly, the specific enrichment of genes in immune-related pathways was revealed when we focused our analysis on genes located near PC-PMD boundaries.…”
Section: Discussionmentioning
confidence: 99%